A hatalommegosztás bibliai gyökerei - Mészáros, István László (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The study points out that although not explicitly named or fully formulated as a concept, the embryonic form of the separation of powers already appears in the Bible. It is reflected in the state-building provisions of the Mosaic Laws, in the way Deuteronomy divides the authority over the people in biblical Israel into four branches, namely: the judges, the king, the priesthood and the prophets. Although the provisions for each of these sectors are presented without a theoretical explanation, it is clear from the prophetic and historical books of the Old Testament that they had a role in keeping power in check. In contrast to the despotic political systems of the time, this served to prevent the concentration of power in a single hand. Furthermore, the biblical anthropology of the New Testament, which emphasizes the depravity of human nature due to original sin and the consequences of the resulting distortions of character, led Christian thinkers and political theorists such as James Madison, who played a leading role in the drafting of the Constitution of the United States of America and its first ten amendments (Bill of Rights 1791), to articulate the need to limit power by power. In conveying all this, the Bible itself has also played a significant role in shaping the separation of powers into a constitutional principle.